1993
DOI: 10.1029/92jb01590
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility of the Mont‐Louis andorra ilmenite‐type granite (Pyrenees): A new tool for the petrographic characterization and regional mapping of zoned granite plutons

Abstract: We have observed remarkably consistent patterns of concentric zonation in the values of low-field magnetic susceptibility measurements over the Variscan age Mont-Louis Andorra granite pluton of the eastern Pyrenees of Andorra, Spain and France. This zonation is a function of the rock petrology since a close correlation is shown between the petrographic nature (as defined by chemical analysis) and the magnetic susceptibility magnitude of the rocks. It reflects the dominantly paramagnetic nature of the granite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 25 publications
7
67
0
2
Order By: Relevance
“…The lineations are the best indicators of the stretching direction to which the magma was subjected while the mineral fabric was forming [4,45,46]. This interpretation is strongly supported by the mafic dykes that crosscut the pluton in the very northwest of Boroujerd perpendicular to the magmatic lineations (Figure 8; [47]). From a structural point of view, it is concluded that the plutons were subjected to an overall protracted N-S to NNW-SSE stretching regime during emplacement and cooling.…”
Section: Microstructuressupporting
confidence: 48%
See 1 more Smart Citation
“…The lineations are the best indicators of the stretching direction to which the magma was subjected while the mineral fabric was forming [4,45,46]. This interpretation is strongly supported by the mafic dykes that crosscut the pluton in the very northwest of Boroujerd perpendicular to the magmatic lineations (Figure 8; [47]). From a structural point of view, it is concluded that the plutons were subjected to an overall protracted N-S to NNW-SSE stretching regime during emplacement and cooling.…”
Section: Microstructuressupporting
confidence: 48%
“…In the low susceptibility granite plutons, such as the Boroujerd, the magnetic susceptibility is regarded as a tool for petrographic characterization and regional mapping [47]. The study of Boroujerd shows that there is good correlation between magnetic susceptibility and the modal classification of Streckeisen (1976) through the iron-content of the rock.…”
Section: Magnetic Parameters Versus Rock-typesmentioning
confidence: 96%
“…For all these reasons, the application of AMS in calc-alkaline plutons (non-magnetic; iron is fractioned mostly in biotite) has represented a turning point in the interpretation of the kinematics of their emplacement modes (Bouchez, 1997). Apart from being able to precisely determine the preferred orientation of biotites in apparently isotropic rocks (a main marker of the rock fabric), AMS also yields a control of the deformation intensity (relative differences among the AMS ellipsoids) and can be used as a petrological mapping variable, being correlated with iron content (Gleizes, Nédélec, Bouchez, Autran, & Rochette, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The antiferromagnetic contribution, typically provided by hematite and goethite, is negligible in practice. The ferromagnetic contribution is commonly a major component and it is associated with magnetite and occasionally with sulfides such as pyrrhotite [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The base of the method is the measure of the orientation and intensity of the magnetic susceptibility (K) of a rock sample whose intensity is the sum of the diamagnetic, paramagnetic, antiferromagnetic and ferromagnetic responses of constituent minerals [3]. The diamagnetic response is typically very weak, and opposes the applied field; this response is typically contributed by iron-free silicates such as quartz and feldspar.…”
Section: Introductionmentioning
confidence: 99%